Hippocampal Subfield Volumes in Patients With First-Episode Psychosis. (9th October 2017) - Baglivo, Valentina; Cao, Bo; Mwangi, Benson; Bellani, Marcella; Perlini, Cinzia; Lasalvia, Antonio; Dusi, Nicola; Bonetto, Chiara; Cristofalo, Doriana; Alessandrini, Franco; Zoccatelli, Giada; Ciceri, Elisa; et al.
Abstract: Background: Hippocampal abnormalities have been largely reported in patients with schizophrenia and bipolar disorder, and are considered to be involved in the pathophysiology of the psychosis. The hippocampus consists of several subfields but it remains unclear their involvement in the early stages of psychosis. Aim: The aim of this study was to investigate volumetric alterations in hippocampal subfields in patients at the first-episode psychosis (FEP). Methods: Magnetic resonance imaging (MRI) data were collected in 134 subjects (58 FEP patients; 76 healthy controls [HC]). A novel automated hippocampal segmentation algorithm was used to segment the hippocampal subfields, based on an atlas constructed from ultra-high resolution imaging on ex vivo hippocampal tissue. The general linear model was used to investigate volume differences between FEP patients and HC, with age, gender and total intracranial volume as covariates. Results: We found significantly lower volumes of bilateral CA1, CA4, and granule cell layer (GCL), and of left CA3, and left molecular layer (ML) in FEP patients compared to HC. Only the volumes of the left hippocampus and its subfields were significantly lower in FEP than HC at the False Discovery Rate (FDR) of 0.1. No correlation was found between hippocampal subfield volume and duration of illness, age of onset, duration of medication, and Positive and Negative Syndrome Scale (PANSS). Conclusion: We report abnormally low volumes of left hippocampal subfields in patients with FEP, sustaining its role as a putative neural marker of psychosis onset.